Analysis of the effectiveness of different schemes of supportive therapy in the prophylaxis of cisplatin-induced nephrotoxicity - Vítor Henrique COSTA; Inajara ROTTA; Gisele Paula SOUZA; Letícia Mastrangelo COELHO; Juliane CARLOTTO (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2024)
Objective: To evaluate, in the scenario of rapid infusion, the effectiveness of the different regimens of supportive therapy employed in the prevention of nephrotoxicity and electrolyte depletion induced by cisplatin (CDDP). Methods: Data from patients who used CDDP weekly (30 to 40mg/m2) with an infusion time of 60-120 minutes were analyzed. The regimens evaluated were: saline solution (A), saline solution and mannitol (B), saline solution and magnesium (C) and saline solution with mannitol and magnesium (D). The following laboratory parameters were evaluated: creatinine (Cr), magnesium (Mg) sodium (Na) and potassium (K), and glomerular filtration rate (GFR). They were subsequently compiled in Microsoft Office Excel® and analyzed in Software R, using with analysis by means of descriptive statistics, developed in accordance with the recommendations of Strengthening the Reporting of Observational studies in Epidemiology (STROBE) statement. Results: The study population evaluated were 46 patients, who received 218 infusions of CDDP. It was observed that schemes A and B had a progressive decrease in Mg. Scheme B had decreased levels of K, Cr and increased Na. In the individual analysis of each cycle, the different schemes of supportive therapy in rapid infusion were equally effective in preventing nephrotoxicity and electrolyte depletion. The schemes used were evaluated for throughout CDDP administrations, the regimen C and D demonstrated efficacy in maintaining renal function throughout multiple administration of CDDP. Conclusion: In the analysis of cumulative doses, regimen C proved to be effective in preserving renal function throughout CDDP administrations. In the individual analysis of each cycle, regardless of the number of times CDDP was administered, protocols C and D, which contained Mg supplementation associated or not with mannitol, were equally effective in preventing nephrotoxicity.